Penetration of Biodentine, NeoMTA 2, and NeoPUTTY into dentinal tubules in primary tooth pulpotomy: a confocal laser scanning microscopy analysis - Merve Ozdemir; Aysenur Oncu (BMC Oral Health)
Abstract Background Pulpotomy is an accepted treatment option to preserve primary teeth with exposed pulp due to caries or trauma and to ensure proper function until physiologic exfoliation. This study aimed to assess the dentin penetration of NeoMTA 2, NeoPUTTY, and Biodentine using confocal laser scanning microscopy (CLSM). Methods The present study was performed using 42 freshly extracted lower primary molars. All samples were divided into 3 separate groups and the Biodentine, NeoMTA 2, and NeoPUTTY were placed on the cavity floor, respectively. High-speed diamond discs were used to create 2-mm-thick sections from the furcation region, including a 1- mm crown and 1-mm root. Primary molar tooth sections were placed on a glass slide and examined using a CLSM (LSM 980, Zeiss, Germany). All images were analyzed using ImageJ/Fiji (National Institute of Health, USA) software for the measurement of penetration depth. The penetration depth of the materials was evaluated using one- way ANOVA, and the Tukey test was used for comparisons between groups at p < 0.05 significance level. Results There was no significant difference in penetration depth between the Biodentine and NeoMTA 2 materials. NeoPUTTY showed higher penetration depth than Biodentine and NeoMTA 2. Conclusions This study reported that NeoPUTTY showed higher dentinal tubule penetration in primary teeth than NeoMTA 2 and Biodentine as pulpotomy materials.